PERAN ADVOKAT DI PENGADILAN AGAMA: Studi di Pengadilan Agama Padang Kelas I A - Masna Yunita (Universitas Islam Negeri Imam Bonjol Padang, 2014)
In 2003, the government issued the law no.18 on the lawyer that creates a new opportunity for the graduatesof the Sharia Faculty to become a lawyer for the court. Before this year, this profesion was a privilage to thegraduates of the Law Faculty. Data shows that there are only two lawyers graduated from the Sharia Faculty’swho have become this profession. Thus, it is necessary to observe how they run their role in giving legal advicesto the parties, and also to examine the preferences of the clients between the lawyers graduated from the Shariahfaculty and the Law Faculty. This study reveals that the lawyers graduated from the Sharia Faculty tend tohave clients who were exercising the case in the Islamic Court rather than other courts. Further, the clients’spreference is mostly to the lawyers graduated for the Faculty of Law. It suggests that it requires to stimulate thestudents of the Sharia Faculty to be interested to become a lawyer.